Lessons in Fiscal Consolidation for the Successor States of the Soviet Union - Kopits, George (IMF Working Papers; Working Paper ;, 1993)
This paper reviews lessons in fiscal consolidation for the former Soviet Union that emerge from the experience of Central and Eastern European economies in transition. A central lesson is the need to support the macroeconomic stabilization with a front-loaded fiscal adjustment. Consistent with this adjustment path, structural reform in the tax and expenditure areas should be aimed at allocative efficiency and fairness, and its sequencing be predicated largely on administrative constraints. In the face of the uncertainty of fiscal projections, formulation of contingency measures is necessary. In addition, elimination of submerged fiscal imbalances, stemming from quasi-fiscal activities of state-owned nonfinancial enterprises and financial institutions, is just as important as correcting the measured budget deficit.